Clinical and psychiatric profile of burn victims from suicide attempts: An integrative literature review (Research, Society and Development, 2025)
Self-inflicted burns resulting from suicide attempts represent a severe public health concern, often linked to intense psychological distress, impulsivity, and barriers to specialized mental health care. This study aimed to identify the clinical and psychiatric profile of burn victims who attempted suicide. An integrative review was conducted using the Virtual Health Library (VHL), with the descriptors “burns” AND “suicide.” The initial search yielded 68 articles; after applying inclusion criteria (full text, quantitative studies), 15 articles were reviewed in full. Results indicated a predominance of female victims (77.8%), especially among individuals aged 15–24 years (36.8%). Alcohol was the primary etiological agent (85.2%), functioning both as a combustible substance and as a facilitator of disinhibition and suicidal impulsivity. Psychiatric diagnoses were present in 95% of cases, most notably major depressive disorder (69%) and anxiety disorders. Additionally, 23% of victims had alcohol use disorder and 21.4% reported previous suicide attempts, reflecting a high risk of recurrence. Contemporary literature suggests that such behaviors cluster in populations marked by emotional vulnerability, limited social support, and high exposure to interpersonal violence. Findings highlight that self-inflicted burn injuries constitute a complex and multifactorial phenomenon requiring integrated interventions, including psychiatric treatment, pain management, psychosocial support, and strengthened protection networks. Future studies should explore cultural factors and gender dynamics that influence the choice of burns as a suicidal method.